RadioImmunotherapy for adenoid cystic carcinoma: a single-institution series of combined treatment with cetuximab - Jensen, Alexandra; Krauß, Jürgen; Weichert, Wilko; Debus, Jürgen; Münter, Marc (Radiation oncology, 2010)
Local control in adjuvant/definitive RT of adenoid cystic carcinoma (ACC) is largely dose-dependent. However, some clinical situations do not allow application of tumouricidal doses (i.e. re-irradiation) hence radiation sensitization by exploitation of high endothelial growth factor receptor (EGFR)-expression in ACC seems beneficial. This is a single-institution experience of combined radioimmunotherapy (RIT) with the EGFR-inhibitor cetuximab.